Neurosurgery Elective for Preclinical Medical Students With and Without a Home Neurosurgery Program. (1st September 2019) - Dallas, Jonathan; Mummareddy, Nishit; Yengo-Kahn, Aaron M; Dambrino, Robert J; Lopez, Alexander M; Chambless, Lola Blackwell; Berkman, Richard; Chitale, Rohan V; Bonfield, Christopher M; Offodile, Regina S; Wellons, John C; Thompson, Reid C; et al.
Abstract: INTRODUCTION: Early medical student exposure to neurosurgery through preclinical electives has been shown to improve recruitment, yet the effect on students without a home neurosurgery program is unknown. We conducted a preclinical neurosurgery elective in a mixed cohort of students with and without a neurosurgery program to 1) evaluate pre- and postelective neurosurgery perceptions, 2) discern differences between cohorts, and 3) identify important factors in those considering neurosurgery a career. METHODS: A yearly neurosurgery elective was offered to students enrolled at the Vanderbilt University School of Medicine (VUSM; home program) or Meharry Medical College (MMC; no home program) from 2017 to 2018. Each class included three components: student-led presentation, faculty academic lecture, and faculty nonacademic discussion. Pre- and postcourse surveys were completed. RESULTS: Thirty-two students completed the course. Postcourse surveys showed that both VUSM and MMC students felt more educated about the field/subspecialties, research, and practice settings. VUSM students showed no changes in perceptions of the field, whereas MMC students had multiple improved perceptions, including neurosurgery's future ( P  = .025), personalities and collegiality ( P  = .001), and achievability of family ( P  = .010). A total of 14 (44%) students showed a significant increase in considering neurosurgery as a career, 8 of which (57%) were in the MMC group. Students more likely to consider neurosurgery as a career showed a significant improvement in the level of emotional draining ( P  = .042), personalities and collegiality ( P  = .003), and achievability of family ( P  = .001), but not residency difficulty ( P  = .102) or financial security ( P  = .380). Those whose interest was neutral/decreased after the course showed no changes in these perceptions. CONCLUSION: Early exposure to neurosurgery at medical schools without a home department may improve students' preconceived notions and attitudes about neurosurgery. Preclinical electives provide valuable, accurate information about the benefits and rigors of neurosurgery, allowing students to make informed decisions about pursuing the field further. This first-hand experience may broaden the net of residency recruitment.